SEVERE FORM OF HYPERTRIGLYCERIDEMIA - Mucha, Argjent; Bitoska, Iskra; Jovanovska Mishevska, Sasha; Mladenovska Sotjkoska, Ivana (My University, 2022)
Hypertriglyceridemia, fenofibrates, pancreatitis. А 39 years old male first control due to high triglycerides. Previosly was hospitalized at Clinic of Gastroenterohepatology, because he was complaining for abdominal pain and on a random labatory finding lipemic serum was spotted. He had negative history of other diseases (DM, hypothyreosis, cholecystitis) and negative family history of coronary arterial disease. He was smoking 30 cigarettes per day, and no alcohol. He was obese, BMI 38 kg/m2 and was diagnosed with acute pancreatitis. Abdominal ulstrasonography: steatotic liver, pancreas easily oedematous. Labaratory findings: glycemia-6.7 mmol/L; ALT-64, amilaza (s)-76, LDH-478, GGt-90, TG-31 mmol/l; cholesterol-7.6, HDL-0.7, LDL-6. His current therapy was: statins 20 mg per day, H2 blockers. Because of very high values od TG we started with intravenous fluid therapy (5 % dextrosis 500 ml) with small dosages of insulin five days, and after that we continued with fenofibrate 145 mg per day, statins 20 mg per day, and omega-3 fatty acids. After 3 months TG values: 7.2, LDL: 4.4, HDL: 0.9. Discussion: Each patient with elevated TG should be evaluated for a secondary cause (endocrine disorders or drugs). Patients with primary hypertrygliceridemia should be monitored for cardiovascular risk factors (central obesity, HTA, hepatic dysfunction), and for familial dyslipidaemia and cardiovascular disease, in order to confirm the genetic cause and cardiovascular risk. According to the findings, the patient’s treatment should include: diet, statins, fenofibrate, niacin, omega-3 fatty acids. Conclusion: Therapy with fibrates should be the first line of choice in patients at risk for pancreatitis. The three drugs (fibrates, niacin, n-3 fatty acids) alone or in combi